Lead induces oxidative stress and phenotypic markers of apoptosis in Saccharomyces cerevisiae - Bussche, Jurrian Vanden (2017)
In the present work, the mode of cell death induced by Pb in Saccharomyces cerevisiae was studied. Yeast cells Pb-exposed, up to 6 h, loss progressively the capacity to proliferate and maintained the membrane integrity evaluated by the fluorescent probes bis(1,3- dibutylbarbituric acid trimethine oxonol) and propidium iodide. Pb-induced death is an active process, requiring the participation of cellular metabolism, since the simultaneous addition of cycloheximide attenuated the loss of cell proliferation capacity. Cells exposed to Pb accumulated intracelullarly reactive oxygen species (ROS), evaluated by 2′,7′-dichlorodihydrofluorescein diacetate. The addition of ascorbic acid (a ROS scavenger) strongly reduced the oxidative stress and impaired the loss of proliferation capacity in Pb-treated cells. Pb-exposed cells displayed nuclear morphological alterations, like chromatin fragmentation, as revealed by diaminophenylindole staining. Together, the data obtained indicate that yeast cells exposition to 1 mmol/l Pb results in severe oxidative stress which can be the trigger of programmed cell death by apoptosis.